How Interest Rates Redistribute Income - Blair Fix (Economics from the Top Down, 2023)
When I read about monetary policy, I have a rule of thumb. Every time I see the phrase interest rate, I replace it with the term wage rate. Then I ask myself whether the discussion still makes sense. Often, it does not. The reason I make this substitution is that in conceptual terms, the interest rate and the wage rate are similar: they are both rates of return. Wages are the return on employment. Interest rates are the return on credit. Now, the important thing about rates of return is that when we change them, we are toying with the distribution of income. Hike wages and we send more income to workers. Hike the rate of interest and we send more income to creditors. Sure, the specifics of this redistribution are open for inquiry. But by definition, rates of return are `distributional variables' — they determine how the income pie gets divvied up. Back to my word substitution. When it comes to wages, the issue of distribution is typically front and center. That's why talk of a minimum-wage hike prompts businesses (and many economists) to complain about reduced profits. But when creditors hike the rate of interest, talk of income distribution is curiously absent. Instead, we get a barrage of macroeconomic jargon — terms like the `natural rate of interest' and the `non-accelerating inflation rate of unemployment'. Why the discrepancy? One possibility is that economists know something that we don't. Perhaps they've looked at the evidence and concluded that interest rates have a `neutral' effect on the distribution of income. Another possibility is that the macroeconomic jargon is mostly a distraction. In other words, like wages, the rate of interest is a `distributional variable'. But it's one that mainstream economists prefer to ignore. So which option is true? In this post, I let the evidence speak for itself. Looking at cross-country evidence, I find that interest rates are decidedly non-neutral. As interest rates rise, three things happen: (1) the interest share of income increases; (2) the labor share of income decreases; (3) income inequality increases. In short, the evidence suggests that interest rates play a key role in the game of class warfare. And that makes sense. Interest, after all, is a rate of return. And when it comes to divvying up the income pie, rates of return are always zero sum.
Keywords: E5; J3; E4; 330; credistors; distribution; interest rates; labour; wages